Cameroon Economic Update, January 2012 : Unlocking the Labor Force, An Economic Update on Cameroon with a Focus on Employment - World Bank (World Bank, Cameroon, 2017)
With this Cameroon economic update, the World Bank is pursuing a program of short, crisp and frequent country economic reports. These economic updates provide an analysis of the trends and constraints in Cameroon's economic development. Each issue, produced bi-annually, provides an update of recent economic developments as well as a special focus on a topical issue. The economic updates aim to share knowledge and stimulate debate among those interested in improving the economic management of Cameroon and unleashing its enormous potential. The notes thereby offer another voice on economic issues in Cameroon, and an additional platform for engagement, learning and change.